Penerapan Teknologi Near Field Communication (NFC) dalam Aplikasi Sistem Navigasi Pariwisata di Kecamatan Sampolawa Berbasis Android - Azlin, Azlin; Asmiddin, Ahmad Maulid; Sabowaka, La Ode Murizal (Informatics Engineering Department, Dayanu Ikhsanuddin University, 2025)
Sampolawa District is one of the regions in South Buton Regency, Southeast Sulawesi Province, which has diverse tourism potential, including natural tourism, religious tourism, cultural and artistic tourism, and agricultural tourism. However, these tourism destinations are not yet widely known by people from outside the region due to limited information and the relatively remote locations of the tourist sites. This study aims to design and examine the working mechanism of an Android-based tourism navigation system application in Sampolawa District by utilizing Near Field Communication (NFC) technology. The research methods employed include observation, interviews, and literature review. The results show that the developed application is able to facilitate tourists in accessing tourism information and navigation to tourist destinations. Tourists only need to perform a tapping process on an NFC tag at the desired tourist location, after which the system automatically displays information and navigation routes to the site. The NFC technology applied operates in read/write mode. The process of writing tourism code data into the NFC tag uses Amplitude Shift Keying (ASK) modulation, in which the smartphone transmits a modulated carrier signal at 13.56 MHz that is received by the NFC tag and converted into power to store data in the tag’s memory. Meanwhile, the data reading process employs Load Modulation techniques, enabling the tourism code to be read by the smartphone through the activation of the NFC chip and tag memory.